2022
DOI: 10.1007/s13555-021-00675-w
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Secukinumab for Psoriasis in a Real-World Clinical Setting in the Asia-Pacific and Middle East Regions: Results from the REALIA Study

Abstract: Introduction: Secukinumab has demonstrated sustained long-term efficacy with a favourable safety profile in various manifestations of psoriatic disease. We investigated effectiveness and safety of secukinumab, other biologics and conventional systemic therapies in patients with chronic plaque psoriasis in a real-world setting.Methods: REALIA was a non-interventional, multicentre, prospective, parallel group study. Eligible patients were C 18 years old with chronic plaque psoriasis commencing a new treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
5
3
1
Order By: Relevance
“…The use of biologic agents potentially raises the risk of infection due to their function in the inhibition of IL‐17, which plays an important role in innate and adaptive immune system 29 . A previous real‐world study reported patients receiving secukinumab experienced a slightly increased risk of infection compared to other biologics (e.g., anti‐TNF, anti‐IL12/23, and anti‐IL17A) (16.6% vs. 11.7%) which was, nevertheless, similar to that observed in clinical studies 21,30 . In our study, infection was reported in only 1.2% of our patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The use of biologic agents potentially raises the risk of infection due to their function in the inhibition of IL‐17, which plays an important role in innate and adaptive immune system 29 . A previous real‐world study reported patients receiving secukinumab experienced a slightly increased risk of infection compared to other biologics (e.g., anti‐TNF, anti‐IL12/23, and anti‐IL17A) (16.6% vs. 11.7%) which was, nevertheless, similar to that observed in clinical studies 21,30 . In our study, infection was reported in only 1.2% of our patients.…”
Section: Discussionsupporting
confidence: 85%
“…Our patients' baseline PASI score (15.4) was comparable to those of previous real‐world studies in Asia‐Pacific and Middle‐east regions, Japan, China, and Italy 21–24 . In addition to baseline PASI score, several factors, that is, BSA, DLQI, area of involvement, course of disease, and so forth contribute to physician decision on biologic use 17,18 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Additionally, the results of this study were found to be higher than other real-world evidence studies in European and Asian population with respect to the rate of PASI 75/90/100 and absolute PASI ≤ 3 [ 18 21 ]. The PASI response rates in this study were comparatively higher than REALIA, a real-world study in Asia–Pacific and Middle Eastern patients, who received 12-month secukinumab treatment [ 8 ]. The PASI response rates were sustained after 24 months of secukinumab treatment in this study and were comparable to those reported in the 104-week real-world study by Rompoti et al.…”
Section: Discussionmentioning
confidence: 84%
“…Factors such as presence of existing comorbidities, ongoing concomitant therapies and challenges with access to medicines which directly impact the treatment choice and outcomes differentiate patients in real-world clinical practice from those enrolled in RCTs [ 7 ]. Furthermore, the treatment regimens prescribed by clinicians may differ from the label or current treatment recommendations based on clinicians’ judgement on the benefit–risk profile of secukinumab for individual patients in a real-world setting and the characteristics of local health systems [ 8 ]. Thus, it is essential to evaluate the real-world effectiveness and understand the impact of treatment patterns of secukinumab in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%